Pengembangan Lembar Kegiatan Siswa (LKS) Matematika Berbasis Pendekatan Scientific pada Materi Aritmatika Sosial bagi Siswa SMP - Natalia Rosalina Rawa (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
This research aims to produce a mathematics worksheet book based on a scientific approach in social arithmetic subject that is appropriate for use in seventh grade students of Junior High Schools. The development model was based on the ADDIE development model which included 5 stages namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The research subjects were seventh grade students of Citra Bakti Junior High School. The research instrument consisted of worksheet validation sheets, teacher response questionnaire, student response questionnaire, and observation sheet of learning activities. The quality and feasibility of the worksheet were based on the validity test by two validators and the practicality test was by 10 students of the test subject. Based on the results of data analysis, it was found that the results of the worksheet validity test obtained a validity score 3.21 or 80.2% and were on the validity criteria of "valid". So, it can be concluded that the worksheets that has been developed is valid and the results of the worksheet practicality test obtain an average practicality score of 10 students is 3.56 or 89%. This means that the worksheets developed is categorized into the high practicality criteria. Thus, the mathematics worksheet book based on a scientific approach in social arithmetic subject that is developed is feasible to be used for seventh grade students of Junior High School.